Tales of Doctoral Students: Motivations and Expectations on the Route to the Unknown - Sara Diogo; Andreia Gonçalves; Sónia Cardoso; Teresa Carvalho (MDPI AG, 2022)
This paper provides a reflection on the way changes taking place in doctoral education are being perceived and internalized by doctoral students. The Doctoral perceptions are analyzed through Ph.D. candidates' motivations to enroll in the program and to their levels of satisfaction with the supervision experience. Comparisons between national and international students, as well as differences according to doctoral programs' scientific areas, i.e., between students enrolled in Science, Technology, Engineering and Mathematics (STEM) and in Social Sciences, Languages and Humanities (SSLH) are established. Based on a case study developed in a Portuguese university, conclusions point to the dominance of a romanticized, traditional view of doctoral education, with the academic profession at its core. This view is mostly shared by international students and those from SSLH scientific areas. In turn, national Ph.D. candidates and those from STEM areas have incorporated a more instrumental view of doctoral education, aiming for training participants to professions outside academia.